Care management: agreement between nursing prescriptions and patients' care needs - Marília Silveira Faeda; Márcia Galan Perroca
ABSTRACT Objectives: analyze agreement between nursing prescriptions recorded in medical files and patients' care needs; investigate the correlation between the nurses' professional background and agreement of prescriptions. Method: descriptive study with quantitative and documentary approach conducted in the medical clinic, surgical, and specialized units of a university hospital in the interior of São Paulo, Brazil. The new validated version of a Patient Classification Instrument was used and 380 nursing prescriptions written at the times of hospital admission and discharge were assessed. Results: 75% of the nursing prescriptions items were compatible with the patients' care needs. Only low correlation between nursing prescription agreement and professional background was found. Conclusion: the nursing prescriptions did not fully meet the care needs of patients. The care context and work process should be analyzed to enable more effective prescriptions, while strategies to assess the care needs of patients are recommended.